Valorization of almond shell biomass to biocarbon materials: Influence of pyrolysis temperature on their physicochemical properties and electrical conductivity. (October 2022) - Debevc, Susan; Weldekidan, Haftom; Snowdon, Michael R.; Vivekanandhan, Singaravelu; Wood, Delilah F.; Misra, Manjusri; Mohanty, Amar K.
Highlights: Effect of pyrolysis temperature on ground almond shell was investigated. Carbon content of the samples was increased with increasing pyrolysis temperature. The biocarbon produced at 700 °C exhibits higher electrical conductivity. Electrical conductivity increased with packing fraction and carbonization temperatures. Abstract: Agricultural wastes are presently being used as animal feed or incinerated, yet they have the potential to become eco-friendly, value-added products. Converting agricultural waste into biocarbon material is one of the current advancements in their valorization. Biocarbons exhibit a wide range of application potential. The physical and chemical properties of biocarbons produced from agricultural feedstock differ based on pyrolysis conditions, in which the pyrolysis temperature plays a vital role. In this study, almond shell biomass was carbonized at three different temperatures: 300, 500, and 700 °C. The resulting biocarbons were analyzed to understand the influence of pyrolysis temperature on physicochemical characteristics. The carbon content in almond shells rose from 47% in the raw biomass to 75% in the biocarbon obtained at 700 °C. TGA-FTIR spectra indicated the release of volatiles such as CO2, hydrocarbons, carbonyl groups, and ethers, the release of which increased with increasing temperature. Further, the increased pyrolysis temperature improved the thermal stability of almond shell derived biocarbons. The deconvoluted ID /IG ratios of Raman peaks were calculated to 1.274 and 1.012 for the biocarbons obtained at 500 and 700 °C, respectively, indicating a trend of increasing trubostratic carbons with increasing pyrolysis temperature. The biocarbon produced at 700 °C was 53 times more electrically conductive than biocarbon produced at 500 °C, likely due to the high carbon content and increased structural ordering of the carbons. Graphical abstract: Image, graphical abstract